Positive whole body thyroid scan with negative thyroglobulin in patients with differentiated thyroid cancer after total thyroidectomy: cases report - Morales-Guzmán-Barrón, Rosanna (2019)
Five patients with thyroid cancer and thyroidectomy are reported. In the whole body iodine-131 scan they had positive iodine-131 uptake with negative serum thyroglobulin (Tg). In all cases, remnant thyroid cancer tissue was reported in the muscle adjacent to the laryngeal cartilage, which could explain iodine uptake in spite of negative serum Tg. It is recommended to perform a whole body iodine-131 scan when there is a strong suspicion of microscopic cancer tissue in the remnant tissues.